Mosaicism for GJB1 mutation causes milder Charcot-Marie-Tooth X1 phenotype in a heterozygous man than in a manifesting heterozygous woman - Borgulová, Irena; Mazanec, Radim; Dolinová, Iva; Havlová, Miluše; Šafka-Brožková, Dana; Seeman, Pavel (Neurogenetics, 2013)
Charcot-Marie-Tooth (CMT) disease is a heterogeneous disorder of the peripheral nervous system that collectively affects approximately 1 in 2,500 individuals, thus making it the most common inherited neurologic disorder. X-linked inheritance may account for 10-20 % of CMT neuropathy. We report a Czech family with a 30-year-old woman affected by CMT since the age of 10 years, originally as an isolated case. Nerve conduction study (NCS) showed demyelinating neuropathy, and DNA testing revealed a novel heterozygous gap junction beta-1 protein (GJB1) mutation c.784_786delTA. The same mutation, but surprisingly in heterozygous state, was subsequently found in her subjectively healthy father and later also in one of her sisters but not in her two other sisters. NCS showed intermediate type of motor and sensory neuropathy in these two females manifesting heterozygotes and normal results in the other healthy sisters and one brother, all without the c.784_786delTA mutation. The father has a phenotype milder than his daughter and has only subclinical signs of CMT. The index female patient had normal karyotype 46, XX, and normal FISH for centromeric X chromosome. We concluded that the proband's father is a heterozygote due to the somatic mosaicism for the GJB1 mutation in his leukocytes (detected by DNA sequencing) and also in his germ cells as confirmed by the unexpectedly different genotypes in his four daughters. Quantitative analysis revealed a mutated signal in 25:75 allele proportion of mutated to healthy allele in the mosaic father. This study has important consequences for genetic counseling and prognosis in CMTX1 families.
Keywords: Charcot-Marie-Tooth Disease; konexiny; Adult; Male; lidé; Peripheral Nerves; lidé středního věku; Humans; heterozygot; Middle Aged; Genes, X-Linked; Heterozygote; Czech Republic; mozaicismus; mužské pohlaví; dospělí; Charcotova-Marieova-Toothova nemoc; Mosaicism; Connexins; Česká republika; ženské pohlaví; Female; periferní nervy; geny vázané na chromozom X